Sonographic diagnosis of fetal eye anomalies and their association with syndromal diseases: A retrospective multicenter analysis of 264 cases - Jorge Jiménez Cruz; Paul Böckenhoff; Laura Tascón Padrón; Norah Emrich; Philipp Kosian; Brigitte Strizek; Cristoph Berg; Eva Weber; Ulrich Gembruch; Annegret Geipel (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction This study aims to systematically describe eye malformations and correlate these with extraocular findings. Based on these findings, we propose a protocol for ultrasound evaluation of the fetal eye. Material and Methods In this multicentric retrospective cohort study, 264 fetuses with ocular malformations from two tertiary referral centers for prenatal medicine were analyzed. Anophthalmia, microphthalmia, exophthalmos, hyper‐ or hypotelorism, cataract, aphakia, cyclopia, and retinal detachment were assessed, and their association with extraocular findings and genetic changes was investigated. Results The majority of the cases (99.2%) were non‐isolated and presented further extraocular findings. Most commonly, the brain and central nervous system (65.9%), the limbs and the heart (46.6% each) and the cranial anatomy (41.2%) were affected. Significant associations were found between exophthalmos and anomalies of the fetal skeletal system (OR = 4.8, 95% CI 1.6–14) and cranial malformations (OR = 3.3, 95% CI 1.5–7.4). Hypotelorism showed an increased risk of cardiac anomalies (OR = 1.8, 95% CI 1.1–3.5) and brain malformations (OR = 2.16, 95% CI 1.2–4.1), with holoprosencephaly being the most common one. Fetuses with microphthalmia were more likely to have anomalies in the renal system (OR = 2.3, 95% CI 1.2–4.3). In 51.4% of the cases, a genetic aberration could be found, among them most frequently trisomy 13. Conclusions There is a significant association between specific fetal eye anomalies and certain extraocular anomalies, as well as genetic changes. Systematic evaluation of the eye using the proposed protocol is simple to learn and highly reproducible and could help to concentrate diagnosis on a certain group of malformations. Data from this study could help to develop targeted diagnostic molecular tools.